TRANSFORMASI DIGITAL DALAM EKONOMI MODERN - Mukhlis Mukhlis; Arsad Arsad; Zainuddin Mukhsin; Sitaman Said (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This paper aims to analyze and describe theoretically the Digital Transformation in the Modern Economy." Based on the fact that we live in a digital era in all aspects of life (including the economy). Buyers and sellers meet virtually on a digital market platform via an internet connection so that market interactions can occur "anytime and anywhere". This article uses the literary method, namely writing without having to carry out field research, simply examining various relevant references to answer the research objectives. The conclusion of this paper is that digital transformation has fundamentally changed an economic organization and created new value and responded effectively and efficiently to market changes. This transformation has an impact on increasing operational efficiency, product and service innovation, increasing workforce productivity, and global access to markets. Digital transformation is causing the loss of traditional jobs, security and privacy, monopolies and oligopolies, and dependence on technology as well as increasing social inequality. The relationship between internet penetration and economic development is increasingly evident, where economic growth and richer economic conditions tend to be more able to absorb and utilize the internet effectively and efficiently for economic needs.